2011
DOI: 10.1074/jbc.m110.167965
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β2-Microglobulin Amyloid Fibril Formation by α2-Macroglobulin

Abstract: The relationship between various amyloidoses and chaperones is gathering attention. In patients with dialysis-related amyloidosis, ␣ 2 -macroglobulin (␣2M), an extracellular chaperone, forms a complex with ␤ 2 -microglobulin (␤2-m), a major component of amyloid fibrils, but the molecular mechanisms and biological implications of the complex formation remain unclear. Here, we found that ␣2M substoichiometrically inhibited the ␤2-m fibril formation at a neutral pH in the presence of SDS, a model for anionic lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
1
20
1
Order By: Relevance
“…As for the other ECs, α 2 M appears to suppress amyloid formation by interacting with prefibrillar species that occur early in the aggregation process (86). A recent study showed that mildly acidic pH or 0.5 mM sodium dodecyl sulphate (which induce dissociation α 2 M tetramers into dimers), increased the binding of α 2 M to β 2 -microglobulin (114). This report proposed that dimeric α 2 M may be more chaperoneactive than the tetramer, however, currently it is unknown whether α 2 M dimers are generated in humans in vivo.…”
Section: α 2 -Macroglobulin (α 2 M)mentioning
confidence: 99%
“…As for the other ECs, α 2 M appears to suppress amyloid formation by interacting with prefibrillar species that occur early in the aggregation process (86). A recent study showed that mildly acidic pH or 0.5 mM sodium dodecyl sulphate (which induce dissociation α 2 M tetramers into dimers), increased the binding of α 2 M to β 2 -microglobulin (114). This report proposed that dimeric α 2 M may be more chaperoneactive than the tetramer, however, currently it is unknown whether α 2 M dimers are generated in humans in vivo.…”
Section: α 2 -Macroglobulin (α 2 M)mentioning
confidence: 99%
“…Recently, the mechanism of amyloid fibrillation under physiological pH conditions has been focused on. 18,[25][26][27][28] Amyloid fibrillation consists of nucleation and growth. 16,24,29,30) The nucleation process, in which a number of monomers associate to form a minimal fibril unit, does not readily occur.…”
Section: Introductionmentioning
confidence: 99%
“…Although our understanding of extracellular proteostasis has increased in recent years, it is still limited compared with our extensive knowledge of the mechanisms comprising intracellular proteostasis (12). Several in vitro studies have shown that α 2 M can inhibit both fibril formation by amyloidogenic proteins and peptides (13)(14)(15)(16) and stress-induced amorphous aggregation of other systems (17). In addition, recent studies have shown that α 2 M can protect neurons from toxic oligomers of the protein HypF-N and the Alzheimer's diseaserelevant amyloid β-peptide (Aβ ) by preventing them from binding to the cell surface (18,19).…”
mentioning
confidence: 99%